The Role of Naqshbandi Sufis of Dera Ghazi Khan in the Preservation and Promotion of the Religious Thought of Mujaddid Alf Thani : مجدد الف ثانی ؒ کی مذہبی فکر کےتحفظ و فروغ میں ڈیرہ غازی خان کے صوفیاء نقشبند کا کردار - Manzoor Husain; Manzoor Ahmad; Dr Najamuddin Bhutto (Al-Bahis Journal of Islamic Sciences Research, 2025)
The preservation and dissemination of the religious thought of Mujaddid Alf Thani (Shaykh Ahmad Sirhindi) has remained a subject of great significance both during his lifetime and in subsequent centuries. His reformist movement sought to safeguard the fundamental Islamic beliefs of Tawheed, Prophethood, and the Hereafter, establishing a clear and firm stance against deviations and innovations. His intellectual and spiritual efforts provided a solid foundation for the stability of Sunni orthodoxy in the Indian subcontinent. The Naqshbandi Sufi order, closely associated with his teachings, played a vital role in spreading and sustaining his reformist vision across various regions. In the southern Punjab region, particularly in Dera Ghazi Khan, Naqshbandi Sufis became instrumental in promoting Mujaddid Alf Thani’s religious ideology. They combined spirituality with social reform, emphasizing purification of the soul, remembrance of Allah, and strict adherence to Shariah. Their contributions not only reinforced the reformist legacy of Mujaddid Alf Thani but also shaped the religious and cultural fabric of the region. This study critically explores the intellectual and spiritual influence of the Naqshbandi Sufis of Dera Ghazi Khan in preserving and transmitting the teachings of Mujaddid Alf Thani in the local context.